Rethinking Indonesia’s Geothermal Foreign Direct Investment Policy: Certainty and Economic Analysis of Law Perspective - Putri, Dinda Silviana; Arsalan, Haikal; Huang, Nikita Kimberly (Hang Tuah Law Journal, 2024)
This study aims to anylize Indonesian government policy regarding the 100% ownership over geothermal sector projects by foreign direct investors, based on the certainty and effectivity using economic analysis of law perspective. This study is formulated as legal research, using statutory approach, conceptual approach, and comparative approach, as research method. The results of this Based on these explanations, it can be concluded that in terms of certainty, renewable energy investment policies in Indonesia, which frequently change, ultimately reduce the value of that certainty. This is different from Germany which tends to be more stable because it has a renewable energy policy that does not change too often, for example this can be seen in German policy regarding providing incentives to foreign investors. Furthermore, regarding the effectiveness of the policy of 100% ownership by foreign investors for geothermal development projects, based on EaL and game theory, this policy can be said to be effective. However, improvements are needed so that the policy does not conflict with SoNR principles. This improvement, for example, is by using the BOOT scheme used by the Philippines in relation to the geothermal development sector, not only can it be 100% owned by foreign investors without a certain period of time.